A novel and sensitive method for determination of amisulpride in human plasma by two‐dimensional liquid chromatography. (20th May 2021) - Qu, Kankan; Wang, Feng; Du, Zhiqiang; Wang, Shushan; Zhang, Zhongdong; Shen, Yuan
Abstract: A novel and sensitive heart‐cutting two‐dimensional liquid chromatography with ultraviolet detection method (2D‐LC–UV) was developed and validated for determination of amisulpride in human plasma. The 2D‐LC system consists of a first dimensional ( 1 D) LC column and a middle transfer column as well as a second‐dimensional ( 2 D) LC column. After simple protein precipitation, the sample was directly injected into the introduction valve of the 2D‐LC system. The 1 D column, playing a role of primary separation and preconcentration for complex plasma matrices, transferred the targets to the intermediate column. Following capture of targets on the middle column online, the analytes were transferred to the 2 D separation column by a six‐port valve. The 2 D column, avoiding interference from the plasma matrix, completed further separation and quantification. An assistant pump was optimized for primary enrichment as well as final elution in the heart‐cutting mode. The analytical time of amisulpride was 7.401 min. The accuracy was between 0.48 and 8.49%, while the intra‐ and inter‐day precisions ranged from 0.9 to 3.1% and from 1.7% to 3.3%, respectively. The linear range of amisulpride was 48.15–2, 407.59 ng/ml, while the extraction recovery was 98.7–101.3%. The strategy established in the study, which was successfully applied to therapeutic drug monitoring of amisulpride for routine clinical detection, displays high sensitivity, good repeatability, convenience and low cost.